THE WOMANLY VOICE OF RACISM AS REPRESENTED IN GWENDOLYN BROOKS'S IN THE MECCA - Al-Douri, Hamdi Hameed; Khalaf, Saba Ali (Al-Adab Journal, 2022)
Gwendolyn Brooks has found herself in a double bind, first because of her "race or ethnicity" as an African American, and at that time because of her femininity. Brooks's writing demonstrates this twofold strain. Brooks is proud of her ethnicity and culture, and she also promotes and celebrates femininity. This study aims to examine the subject of racism in Black American poetry using descriptive techniques by examining certain works by Gwendolyn Brooks. So, Brooks attempts to portray the social injustice and oppression of women of her community that occurred in the 1960s of the 20th century. However, Brooks's modern poetry became an attempt to persuade black people to be heavily associated with their history in order to achieve their essential responsibilities in the community. Furthermore, Brooks emphasizes the need for humanistic respect and love as among the most important prerequisites for a happy life.